The Serabit Expedition of 1930: II. The Mines of Sinai - Barrois, A. (Harvard theological review, 1932)
The district which constituted the field of our investigation is situated on the western slope of central Sinai facing the Gulf of Suez. The remains of ancient mine-workings are divided into two groups of unequal importance: the northern group, of which the numerous openings lie north and south of the upper course of Wadi Baba, and to which belong the mines of the plateau of Serabit, and the southern group, confined to the turquoise galleries of Maghara. The two groups are included in a rectangle which measures about 35 kilometers from east to west and 25 from north to south.